Policy Implementation of The Utilization Priority of Village Fund for Village Development in Bone Regency, South Sulawesi Province - Andi Syarif Hidayatullah Aksa; I Nyoman Sumaryadi; Hyronimus Rowa (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to analyze the implementation and utilization of village fund for village physical facilities and infrastructure in Barebbo, Bone regency, South Sulawesi province. This is a qualitative descriptive study that involves data collection techniques of in-depth interview, documentation, and field observation. When data were collected, the analysis was performed consist of data reduction, data display, and conclusion drawing. The results demonstrate how the implementation of village government in Bone regency complies to the applicable policies issued by national government. The implementation mechanism of Village Fund in Bone Regency for physical facilities and infrastructure passes through several steps, namely village development plan, priority setup, implementation of development program, monitoring and evaluation. However, participation of local community is just for a formality, whereas decision making is still dominated by village head and officials. Village Fund is, however, not utilized and distributed transparently and accountably, and involve active participation of the village community when performing priority setup and supervision of development program. The physical facilities and infrastructure are, in general, made up by the village government quite functionally and finally generate positive feedback from local community and, however, are still in a lower level of sustainability.